Data Traffic Monitoring and Analysis From Measurement, Classification, and Anomaly Detection to Quality of Experience - Biersack, Ernst; Callegari, Christian; Matijasevic, Maja.; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2013)
This book was prepared as the Final Publication of COST Action IC0703 "Data Traffic Monitoring and Analysis: theory, techniques, tools and applications for the future networks". It contains 14 chapters which demonstrate the results, quality,and the impact of European research in the field of TMA in line with the scientific objective of the Action. The book is structured into three parts: network and topology measurement and modelling, traffic classification and anomaly detection, quality of experience.
High-Performance Network Traffic Processing Systems Using Commodity Hardware -- Active Techniques for Available Bandwidth Estimation: Comparison and Application -- Internet Topology Discovery -- Internet PoP Level Maps -- Analysis of Packet Transmission Processes in Peer-to-Peer Networks by Statistical Inference Methods -- Reviewing Traffic Classification -- A Methodological Overview on Anomaly Detection -- Changepoint Detection Techniques for VoIP Traffic -- Distribution-Based Anomaly Detection in Network Traffic -- From Packets to People: Quality of Experience as a New Measurement Challenge -- Internet Video Delivery in YouTube: From Traffic Measurements to Quality of Experience -- Quality Evaluation in Peer-to-Peer IPTV Services -- Cross-Layer FEC-Based Mechanism for Packet Loss Resilient Video Transmission -- Approaches for Utility-Based QoE-Driven Optimization of Network Resource Allocation for Multimedia Services -- Active Techniques for Available Bandwidth Estimation: Comparison and Application -- Internet Topology Discovery -- Internet PoP Level Maps -- Analysis of Packet Transmission Processes in Peer-to-Peer Networks by Statistical Inference Methods -- Reviewing Traffic Classification -- A Methodological Overview on Anomaly Detection -- Changepoint Detection Techniques for VoIP Traffic -- Distribution-Based Anomaly Detection in Network Traffic -- From Packets to People: Quality of Experience as a New Measurement Challenge -- Internet Video Delivery in YouTube: From Traffic Measurements to Quality of Experience -- Quality Evaluation in Peer-to-Peer IPTV Services -- Cross-Layer FEC-Based Mechanism for Packet Loss Resilient Video Transmission -- Approaches for Utility-Based QoE-Driven Optimization of Network Resource Allocation for Multimedia Services.
Keywords: Computer science; Computer Communication Networks; Computer system performance; Computer Science; Computer Communication Networks; System Performance and Evaluation; Information Systems Applications (incl. Internet).